Self-portrait to ID Document face matching: CNN-Based face verification in cross-domain scenario - Costa, Filipe; Melo, Marcos Vinícius L.; Gadelha, Igor; Fôlego, Guilherme; Gambaro, Larissa; Rodrigues, André (Anais do Workshop de Visão Computacional (WVC); 2021: Anais do XVII Workshop de Visão Computacional, 2021)
Face verification approaches determine whether two given faces are from the same person. Recently, a new demand for face verification application which has become popular in commercial applications is the self-portrait and ID face matching, in which we compare the faces of a selfie shot by a subject and the face in a picture of her identification document. In this work, we proposed a novel approach for face verification in a cross-domain scenario, assuming we have only two images for each subject in the dataset. The method is based on siamese architecture with triplet-loss function. Experiments show the proposed model reaches good effectiveness for cross-domain face verification with low error rates, in comparison to other works of the literature.